Correction of requests in the information system decision support - S. F. Lipnitsky (Informatika, 2023)
Objectives. The problem of mathematical modeling and algorithmization of the processes of correction of requests in the system of information support for decision-making is being solved. At the same time, three main goals are pursued: building of a generalized information retrieval model, development of algorithms for pre-search query correction and development of algorithms for post-search query correction.Methods. Methods of set theory and probability theory are used.Results. A generalized information retrieval model has been developed. Within the framework of the model, the concepts of search function, issuance criterion, relevance and pertinence of search results are formalized. Algorithms for pre-search and post-search correction of queries in the information decision support system are proposed.Conclusion. A mathematical model for correcting user requests in the information decision support system has been developed. Within the framework of the model, the efficiency of search processes in terms of the relevance and pertinence of the information found has been studied. Necessary and sufficient optimality of search functions are proved.